Assistance in Preparation of Feasibility Proposal for Catfish Cultivation in Sampora Village - Christine Natalia; Ronald Sukwadi; Maria Angela Kartawidjaja; Marsellinus Bachtiar W; Stanislaus S. Uyanto (MITRA: Jurnal Pemberdayaan Masyarakat, 2020)
The catfish farming business is one of the fastest-growing business of the agriculture fish market today. Catfish consumption is increasing because of its good taste and affordable price. Also, catfish has high protein, low in calorie and fat. However, to get more profits, cost planning is needed, as well as accurate filing of activities and costs for business sustainability. The present community service program aimed to assist how to make a feasibility proposal before starting a catfish business and also to measure the level of understanding and satisfaction of the participants of the program, who were members of the Sampora Village youth organization. The program was implemented at the Statistics and Decision Making Laboratory, Department of Industrial Engineering, AJCUI. The results show that the level of participants’ understanding in analyzing the feasibility of catfish farming increased significantly after attending the training. The participants’ satisfaction with the program was as follows: 76% very good, 19% good, and 5% neutral